If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 6 = 10.2 Reorder the terms: 6 + 5x = 10.2 Solving 6 + 5x = 10.2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 5x = 10.2 + -6 Combine like terms: 6 + -6 = 0 0 + 5x = 10.2 + -6 5x = 10.2 + -6 Combine like terms: 10.2 + -6 = 4.2 5x = 4.2 Divide each side by '5'. x = 0.84 Simplifying x = 0.84
| 0.3x+0.03x+0.003x+0.0003+....=3 | | 11=4+-x | | x=12+-3y | | 5x+10x-2=3(5x+4) | | 75=48+y | | 2p-30=-4p+5 | | Xa-by=c | | 1/2x-20=1/3x | | 5x+5=14+x | | -31=4x+-11-9x-19 | | 2(x+2)+11=29 | | 79+x+51+x+66=180 | | 7+4q=5q | | (3-y)i=4i | | -22+5x=14 | | 0.2(x-3)=0.1(x-5) | | x^2+50x+600=0 | | 6(x+1)+4=2(3x+5) | | 350x=875 | | 100=5(5+x) | | P=2(v+3)+5x | | 0g=1 | | 21-8x=3(1+6)-6 | | f(x)=4x^3-3x^2-19x+99 | | 4y^2+Xy=8 | | 0=6x^2+7x | | 10x-x=1 | | 7(4x-2)+5=28x-9 | | -2(-5+8)= | | 5r+14=86-4r | | (4x+5z)(7x-5z)= | | 49x^2-24x=0 |